Preliminary Numerical Simulation of Acoustic Reflection Imaging Logging While Drilling Based on the Vertical Incidence of Acoustic Waves on the Borehole Wall - LIU Xien; ZHAO Teng; CHE Xiaohua (Cejing jishu)
The current acoustic reflection imaging logging while drilling (LWD) technology is affected by the interference of large amplitude borehole mode waves and the oblique incidence of acoustic waves on the borehole wall, resulting in a long propagation path of echoes. The signal-to-noise ratio (SNR) of the echo signal from the well-side anomalies tends to be low. In response to these shortcomings, an acoustic reflection imaging LWD scheme consisting of the linear phased array acoustic transmitter and its adjacent cylindrical array acoustic receiver is proposed. The downhole linear phased array acoustic transmitter radiates acoustic waves that are incident nearly vertically on the borehole wall, generating as many P-waves as possible in the formation. The acoustic receiver, which is very close to the transmitter, can receive the echo signal from the well-side anomalies propagating along a smaller acoustic path, thereby improving the SNR of the echo signal. In addition, the application of the cylindrical array acoustic receiver can obtain accurate azimuth measurement results. A preliminary numerical simulation study of the proposed method was carried out using a 3D finite difference method. The simulation results show that the acoustic source in the well generates P-waves and S-waves in the formation near the well, where P-waves mainly propagate in the direction perpendicular to the well axis, and S-waves mainly propagate along the upper and lower lateral directions of the well. This indicates that P-waves is more beneficial to detect anomalies that are far away from the well axis. The arrival time of the PP-waves from the formation interface shows an approximate sinusoidal relationship with the azimuth angle of the receiver, and the PP-waves recorded by receivers with different azimuth angles have the same polarity and are similar. The PP-waves received by the receiving unit nearest the formation interface arrives earliest and has the largest amplitude. As the distance between the formation interfaces and the well increases, the arrival time of the PP-waves becomes later and the amplitude becomes smaller. Finally, the new method was compared with the existing methods. The comparison results show that the proposed method can simultaneously suppress borehole mode waves and enhance the energy of formation P-waves outside the well, thereby effectively enhancing the SNR of echo signals. The research provides a theoretical basis for the design of the acoustic reflection imaging LWD tool and subsequent experimental studies.